METHODOLOGICAL FOUNDATIONS OF THE DEVELOPMENT OF PHYSICAL ABILITIES OF STUDENTS - Uraimov Sanjar; Asqarova Nargiza (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article provides information on the results of the development of student’s physical abilities and their manifestation, as the types of activities that require a specific regime for the proper organization and conduct of training.